Degenerate Lattice-Instability-Driven Amorphization under Compression in Metal Halide Perovskite CsPbI3 - Yi, Seho; Lee, Jung-Hoon (American Chemical Society, 2022)
Halide perovskites have been intensively investigated for photovoltaic applications because of their good optoelectronic properties and low cost. Various high-pressure experiments have shown that these materials generally undergo reversible phase transitions between different crystalline phases as well as between crystalline and amorphous phases under external pressure. Herein, using first-principles density functional theory (DFT) and ab initio molecular dynamics (AIMD) calculations, we investigate the origin of the pressure-induced amorphization in CsPbI3. We find that the amorphous-like structures obtained from AIMD calculations become more stable than the orthorhombic Pbnm phase above 6.66 GPa, in good agreement with the experimental value (4.44 GPa). We further find that an imaginary flat band appears in the phonon dispersion of the orthorhombic CsPbI3 phase across the Brillouin zone at 10 GPa, leading to degenerate lattice instabilities. These energetically degenerate phonon modes are related to PbI6 octahedral tilting modes and provide random local distortions, leading to amorphization.